Investment Promotion Essentials : What Sets the World’s Best Investment Facilitators Apart From the Rest - Ortega, Celia; Griffin, Carlos (World Bank, Washington, DC, 2012)
More than 70 percent of investment promotion intermediaries may be missing out on foreign investment by failing to provide investors with accurate and timely information, according to the global investment promotion benchmarking 2009 report. This function, known as 'investment facilitation,' is one of the simplest and most cost effective, yet it is neglected at many agencies. A new survey by the investment climate advisory services of the World Bank Group has identified 14 common practices of the top-performing agencies in the benchmarking study. Weaker performers can inexpensively implement many of these practices to win a larger share of the trillion-dollar market for foreign investment.